ANALISIS KINERJA MESIN PENGAYAK SERAT COCOFIBER - Siswoyo Soekarno; Hamid Ahmad; Muhammad Nasir Afandi (Faculty of Agricultural Technology, University of Jember, 2014)
Fiber Sieving machine is a machine which used for sieving or separating coconut fiber. The machine is made of steel and driven by an electric motor. The purpose of this research was to analyze the quality of cocofiber resulted by sieve machine fiber. The process to produced cocofiber required several stages, there were decomposition, sieving, drying, and packaging. The results showed that increasing the sieve size, generated more cocofiber, less cocopeat, and faster process. Based on ANOVA there were no different between three sieving size treatments (0,4 x 0,4) cm2, (1 x 1) cm2, (2 x 2) cm2).Keywords: sieve machine fiber, efficiency, the size of the sieve